Potensi Karbon Tersimpan Hutan Taman Nasional Gunung Leuser Resort Tenggulun Sebagai Upaya Mitigasi Perubahan Iklim - Zulfan Arico; Sri Jayanthi (Elkawnie, 2016)
Gunung Leuser National Park Resort Tenggulun since 1998-2008 continues to plunder its standing in the way was converted into oil palm plantations. The area was damaged forest of 2,200 hectares / year. This study aims to protect and maintain the forest as a climate change mitigation efforts. The method to determine the location of the study using purposive sampling with squares method to determine the density of vegetation. Furthermore, the method of calculation of the carbon stocks stored calculated using allometric equations. From the results, the results of total forest biomass Gunung Leuser National Park Resort Tenggulun amounted to 330.998 tons / Ha. While the amount of carbon stored by 165.999 tons / Ha